Social Defense Strategy in Handling Maritime Border Issues in Eastern Indonesia (Case Study on Natuna Island) - Pandoe, Ridha Munawir Masly; Sumantri, Siswo Hadi; Suwarno, Panji; Widodo, Pujo (FOCUS, 2024)
Natuna Island, strategically located in the Karimata Strait and the South China Sea, faces significant challenges in managing its maritime borders and social defense. Geopolitical tensions in the region, involving overlapping territorial claims and illegal activities at sea, demand a comprehensive and integrated defense strategy. This study aims to analyze the social defense strategy implemented in Natuna Island by assessing the roles of the central and regional governments, supervision and law enforcement, and empowerment of local communities. The research method used is a literature study, which involves an in-depth analysis of various legal sources, academic literature, and government reports. The results of the study indicate that collaboration between the central and regional governments, the use of advanced technology in surveillance, and empowerment of local communities are key in facing maritime border challenges. This study emphasizes the importance of integration and coordination between various parties to effectively maintain the sovereignty and security of the Natuna Island region.